Concentrations of methylated naphthalenes, anthracenes, and phenanthrenes occurring in Czech river sediments and their effects on toxic events associated with carcinogenesis in rat liver cell lines - Vondrácek, Jan; Svihálková-Sindlerová, Lenka; Pencíková, Katerina; Marvanová, Sona; Krcmár, Pavel; Ciganek, Miroslav; Neca, Jirí; Trosko, James E; Upham, Brad; Kozubík, Alois; Machala, Miroslav (Environmental toxicology and chemistry, 2007)
Alkylated polycyclic aromatic hydrocarbons (PAHs) are important environmental pollutants. In the present study, we determined levels of monomethylated naphthalenes (MeNap), phenanthrenes (MePhe), and anthracenes (MeAnt) in Czech river sediments. The levels of MePhe generally were lower than the concentrations of phenanthrene. In contrast, both MeNap and MeAnt were found at levels higher than their respective parent compounds in the majority of sampling sites. We then investigated their aryl hydrocarbon receptor (AhR)-mediated activity, accumulation of phosphorylated p53 protein, induction of expression of cytochrome P450 1A1 (CYP1A1), inhibition of gap junctional intercellular communication (GJIC), and effects on cell proliferation in rat liver cell models to evaluate the relative importance of these toxicity mechanisms of low-molecular-weight methylated PAHs. Methylated phenanthrene and anthracene compounds were weak inducers of AhR-mediated activity as determined both in a reporter gene assay system and by detection of the endogenous gene (Cyp1a1) induction. 2-Methylphenanthrene was the most potent AhR ligand. Contribution of MeAnt and MePhe to overall AhR-inducing potencies should be taken into account in PAH-contaminated environments. Nevertheless, their effects on AhR were not sufficient to modulate cell proliferation in a normal rat liver progenitor cell model system. These PAHs only had a marginal effect on p53 phosphorylation at high doses of 1-, 3-, and 9-MePhe as well as 1 MeAnt. On the other hand, both 2- and 9-MeAnt as well as all the MePhe under study were efficient inhibitors of GJIC, suggesting that these compounds might act as tumor promoters. In summary, inhibition of GJIC and partial activation of AhR seem to be the most prominent toxic effects of the methylated PAHs in the present study.
Keywords: játra; mezerový spoj; Cytochrome P-450 CYP1A1; Naphthalenes; cytochrom P-450 CYP1A1; receptory aromatických uhlovodíků; regulace genové exprese; Anthracenes; nádorový supresorový protein p53; Dose-Response Relationship, Drug; naftaleny; řeky; krysa rodu Rattus; zvířata; proliferace buněk; Methylation; látky znečišťující životní prostředí; Rivers; anthraceny; Environmental Pollutants; Gene Expression Regulation; Liver; metylace; Carcinogens; Cell Proliferation; Receptors, Aryl Hydrocarbon; Czech Republic; karcinogeny; nádorové buněčné linie; geologické sedimenty; Gap Junctions; Rats; vztah mezi dávkou a účinkem léčiva; Animals; Cell Line, Tumor; Česká republika; Phenanthrenes; fenantreny; Geologic Sediments; Tumor Suppressor Protein p53